Primary subfertility with partial septate uterus and longitudinal vaginal septum (Bangabandhu Sheikh Mujib Medical University Journal, 2017)
A 22 year old married woman presented with the complaints of severe dyspareunia, difficulty in conceiving for 18 months, menorrhagia and dysmenorrhoea since menarche. Clinical examination revealed longitudinal vaginal septum. Ultrasound scan revealed two endometrial cavities with a single cervix. Hysterosalpingogram revealed septum which had separated the endometrial cavity with no free spillage of contrast media on both fallopian tubes. Ultrasound KUB and intravenous urethrography did not reveal any abnormality in the urinary system. Resection of vaginal septum, hysteroscopic septoplasty and diagnostic laparoscopy were performed. Three months after the surgery, she was relieved from the symptoms. However, no comments on fertility issue can be made at the moment as the couple is practicing contraceptive methods.